Quality of Life and Philosophy of Life Determines Physical and Mental Health: Status Over Research Findings From The Quality of Life Research Center, Copenhagen, 1991-2007 - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Quality of life (QOL) has over the past decade become an important part of health science and also increased public awareness. It has become increasingly apparent that illness is closely related to the individual perception of a good life, and therefore the exploration of indicators related to quality of life appears to be of broad importance for the prevention and treatment of diseases. Identifying, which factors constitute a good life may reveal an understanding about what areas in life should be encouraged, in order to enhance the global quality of life, health, and ability. In this paper we present results from studies initiated in 1989 to examine quality of life in relation to disease. The purpose of this presentation was to assemble the results from the study carried out in the years between 1993 and 1997, examining a total of 11.500 Danes, to show the association between quality of life and a wide series of social indicators.